Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx)

Good one!

Generally these are done by changing everything to sines and cosines, unless you see some obvious identities.
Also generally, it is best to start with the more complicated side and try to change it to the "easier" side.

so here goes....

LS=
sinx/cosx ÷ (1-cosx/sinx) + cosx/sinx ÷(1-sinx/cosx)
=sinx/cosx [sinx/(sinx-cosx) + cosx/sinx [cosx/(cosx-sinx)
=sin^2 x/(cosx(sinx-cosx)) - cos^2 x/(sinx(sinx-cosx))
= (sin^3x - cos^3 x)/(sinxcosx(sinx-cosx))
=(sinx-cosx)(sin^2x + sinxcosx + cos^2)÷[sinxcosx(sinx-cosx)] difference of cubes!!!
= (sin^2x + cos^2x + sinxcosx)/(sinxcosx)
= (1 + sinxcosx)/sinxcosx

R.S.= 1+ 1/(sinxcosx)
=(sinxcosx + 1)/(sinxcosx) = L.S

Wow!!
=

thank you very much for your help .

  1. 👍 0
  2. 👎 0
  3. 👁 304
asked by mo

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 vibrations per second, write an equation in the form d=sinw(t) for the simple harmonic motion. 2) Verify the identity tan^2X-cot^2X/tanX+cotX=tanX-cotX I'm not

    asked by Lisa on October 9, 2006
  2. precalc

    tanx cotx ------- + ------- = 1 +secxcscx 1 - cotx 1- tanx prove the proof

    asked by SkiMasktheSlumpGod on February 3, 2018
  3. Trigonometry

    For this question, they want me to use fundamental trig identities to simplify the expression. The problem is as follows; (tanx/csc^2x + tanx/sec^2x)(1+tanx/1+cotx) - 1/cos^2x I got as far as this; tanx(1/csc^2x +

    asked by CodyJinks on July 18, 2019
  4. Pre-Calc

    How do I solve this? My work has led me to a dead end. tan(45-x) + cot(45-x) =4 my work: (tan45 - tanx)/(1+ tan45tanx) + (cot45 - cotx)/(1 + cot45cotx) = 4 (1-tanx)/(1+tanx) + (1-cotx)/(1+cotx) = 4 Then I found a common

    asked by Jess on February 7, 2007
  5. math

    solve each identity algebraically 1)(1-tanx)/(1-cotx)=-tanx 2)(1+cotx)/(1+tanx)=cotx

    asked by Sh on February 24, 2009
  6. a math

    Prove cotx-1/cotx+1 = sec2x - tan2x I prove till cotx-1/cotx+1 =1/1+tanx - tanx/1+tanx

    asked by wang on August 10, 2015
  7. trig

    Verify the trigonometric identity. Please show all steps. tanx-cotx/tanx+cotx=sin^2x-cos^2x

    asked by garrett on March 4, 2012
  8. trig

    verify the identity (tanx+cotx) (1) __________ = ______________ (tanx-cotx) (sin^2x-cos^2x)

    asked by stacey graham on March 26, 2010
  9. matj

    prove that (cotx+tanx)(cotx-tanx) = 1/(sin^2 x) - 1/(cos^x)

    asked by Amir on January 23, 2012
  10. trigonometry

    tanx-cotx/tanx+cotx=1-2cos squardx

    asked by wayne on March 23, 2011

More Similar Questions